A MODEL TO MEASURE EMERGENT LEADERSHIP AMONG EMPLOYEES IN INDONESIA - Siregar, Juliana; Anindita, Rina (Jurnal Aplikasi Manajemen, 2021)
The objective of the research is to develop a model to measure emergent leadership among employees in Indonesia. In doing so, this study first developed a theoretical model by identifying the emergent leadership constructs from the literature and identifying the criteria measurement of these constructs from the literature and thirdly was to validate the theoretical model to measure emergent leadership in Indonesia. The theoretical model consists of 6 emergent leadership constructs measured by a total of 60 measuring criteria. The empirical process of the validation employed data collected from 350 respondents who were working with the team working in Jakarta, Banten, and West Java. The validation aimed to validate the variables that were used to measure each of the constructs by determining statistically that the sample number is adequate; using the Keiser-Meier-Olkin and Bartlett's test to ensure the applicability of the data for multivariate statistical analysis; to validate the measuring criteria as relevant to emergent leadership and to determine the reliability of each of the emergent leadership constructs to the model. The result showed that emergent leadership can be measured by the following indicators: dominant, friendly, egocentric, intelligence, creativity, open mind, experiences, caring, positive vibes, discipline, good planner, conscientiousness, team player, communicative, and performance management for knowledge-skills-attitude. Furthermore, the results of this study found that the variable of the construct performance management from the previous research was in the third dominant value.